Incidence of vitamin D deficiency in pediatric neurology outpatient department of a tertiary care hospital - Karnavat, Purva Keni; Hegde, Anaita Udwadia; Nabi, Fazal (International Journal Of Community Medicine And Public Health, 2018)
Background: Pediatric neurology outpatient populations are a vulnerable subgroup for vitamin D deficiency. The aim was to study the incidence of vitamin D deficiency in pediatric neurology patients by studying relevant biochemical profile and to assess the contributory factors for the same. Methods: A hospital based cross sectional study was conducted at a tertiary care setup in Mumbai between 2011 and 2012. A total of 284 children aged 0.5-18 years, attending pediatric neurology OPD were enrolled. Statistical analysis was carried out with SPSS version 17.0 and included descriptive statistics; Chi squared and unpaired t-tests to investigate significance of proposed predictors for vitamin D status. Results: 89.1% of the children were deficient in vitamin D levels (≤30 ng/ml); out of these 11% were severely deficient. Factors significantly associated with vitamin D deficiency were increasing age (p=0.034), absence of intake of calcium supplements (p=0.00) and upper socio-economic class (p=0.001). Low serum calcium levels (p=0.01) and high PTH levels (p=0.00) were associated significantly. Prevalence was similar in children with higher BMI as compared to lower BMI. Duration of AEDs rather than number of drugs was more associated with deficiency. Conclusions: A high prevalence of vitamin D inadequacy in noted in pediatric neurology patients.